In-cell protease assay systems based on trans-localizing molecular beacon proteins using HCV protease as a model system. - Jeong Hee Kim; Min Jun Lee; Inhwan Hwang; Hyun Jin Hwang (PLoS ONE, 2013)
This study describes a sensitive in-cell protease detection system that enables direct fluorescence detection of a target protease and its inhibition inside living cells. This live-cell imaging system provides a fluorescent molecular beacon protein comprised of an intracellular translocation signal sequence, a protease-specific cleavage sequence, and a fluorescent tag sequence(s). The molecular beacon protein is designed to change its intracellular localization upon cleavage by a target protease, i.e., from the cytosol to a subcellular organelle or from a subcellular organelle to the cytosol. Protease activity can be monitored at the single cell level, and accordingly the entire cell population expressing the protease can be accurately enumerated. The clear cellular change in fluorescence pattern makes this system an ideal tool for various life science and drug discovery research, including high throughput and high content screening applications.